QUALITY CONTROL IN FOREIGN LANGUAGE TEACHING - Irina E. Abramova; Elena P. Shishmolina (Высшее образование в России)
The article analyzes the current situation with foreign language teaching of Russian-speaking students majoring in non-linguistic as well as the lack of a unified evaluation system of the effectiveness of language training provided. The authors describe an assessment model as an integral part of the teaching and learning process. This model is aimed not only at compensating for the lack of the English!language environment but at building the foreign language community at the Russian University.